MEASURING LIVABILITY OF PLOTTED NEIGHBOURHOODS AND APARTMENTS: A STUDY OF PEOPLE’S PERCEPTION (CAHIERS MAGELLANES-NS, 2024)
The 21st century is witnessing diverse changes in several areas of livelihood and housing. Gradually, styles and lifestyles also become more diverse over time. This study attempts to explore the phenomenon of quality of life in the residential areas of the city of Lucknow located in north India. It goes on to examine how satisfied middle-income residents are with their neighborhoods. In addition, it also endeavours to research that through changes in the lifestyle of people living in urban areas, whether in housing estates or low or mid-rise apartments, will bring them quality a better life. A qualitative study was conducted to compare data identified in a cross-sectional survey in identified neighborhoods in Lucknow. The researchers inferred that in the modern context, the acceptance of vertical housing is increasing. In addition, residents of low to mid-rise apartments feel safer, more comfortable and more connected in community life, while also demonstrating the bond between people living together.